Effective low-cost pediatric vision screening by naive nonophthalmic examiners using the ‘Arclight’ device - Rujuta Gore; Jenny N Wang; Christopher D Yang; Miranda An; Stephen C Hunter; Kourosh Shahraki; Andrew Blaikie; Donny W Suh (Indian Journal of Ophthalmology)
Purpose: To explore whether a low-cost ophthalmoscope (Arclight) can be used by naive nonophthalmic examiners to effectively screen for pediatric eye disease. Methods: Fifty-four children (108 eyes) were examined by five medical students using an Arclight. Gold standard examination was performed by an ophthalmologist using a slit lamp and indirect ophthalmoscope. Examinations performed included ophthalmoscopy of the optic disc, estimation of the cup-to-disc ratio (CDR), corneal light reflex test (CRT), Bruckner’s reflex test (BRT), and evaluation of refractive error. We determined the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the nonophthalmologist’s Arclight exam compared to the gold standard findings of comprehensive evaluation by pediatric ophthalmologists. Results: Using the Arclight, the optic nerve exam was successfully completed in 65% of patients. CDRs above and below 0.5 could be determined with 66.7% sensitivity and 84.4% specificity. Arclight CRT measurements were significant (P < .00001) predictors of strabismus, with 80% sensitivity, 95.1%, specificity, 80% PPV, and 95.1% NPV. BRT was not a significant predictor of amblyopia, with a 34.6% sensitivity, 85.7% specificity, 69.2% PPV, and 58.5% NPV. Refractive error was estimated with a success rate of 81% for emmetropia, 38% for myopia, and 21% for hyperopia. The Arclight ease-of-use was rated on average as 4.4 (SD = 0.9) on a scale of 1 to 5, with 1 being the hardest and 5 being the easiest. Conclusions: Our study shows the Arclight as an affordable and effective alternative to the traditional ophthalmoscope for assessing eye disease in children. This device can improve eye health services in under-resourced regions.